Strategies Adopted and Challenges Faced by English Language Teachers in Their Professional Development - Subedi, Lok Nath (Kalika Journal of Multidisciplinary Studies, 2025)
The present study entitled “Strategies Adopted and Challenges Faced by Community Campus English Language Teachers for their Professional Development” is concerned with the English language teachers in the community campus of Pokhara valley. This research used a narrative inquiry and data were collected through semi-structure interviews with five English language teachers from five community campuses of Pokhara valley. The main findings of the study shows that most teachers uses multiple strategies for their professional development like self-monitoring, doing action research, teaching journals, studying research articles, journals, participating in various Language teaching related workshops, seminars and national and international conferences. These involvements enhance their pedagogical skills and make effective classroom teaching. The study also reveals various challenges that create barriers for their professional advancement like time constraints, lack of institutional support, lack of teaching resources, incentives and also the interferences of their students’ native languages. The study also found that the English language teachers of the community campuses of Pokhara valley mostly use traditional teaching strategies basically lecture methods. Likewise, the study also showed that the English language teachers have also faced various challenges while applying new strategies in the English language classroom